Influence of The -202 A/C insulin-like growth factor-binding protein-3 promoter polymorphism on individual variation in height in Korean girls - Min Ju Yi; Tae Young Park; Il Tae Hwang; Seung Yang (Korean Society of Pediatric Endocrinology, 2017)
PurposeThe most common single nucleotide polymorphism in the IGFBP3 promoter region occurs at position -202. This polymorphic variation occurs frequently and may influence growth hormone responsiveness and somatic growth. However, the effects of IGFBP3 promoter polymorphism on growth in children are unknown.MethodsRestriction fragment length polymorphism-based genotyping of the -202 single nucleotide polymorphism was performed in 146 Korean girls aged between 15 and 16 years, who were selected randomly from the Seoul School Health Promotion Center. The participants were divided into 3 groups (tall, medium, and short) according to the height percentile established from normal reference values for Korean children. The serum levels of insulin-like growth factor I (IGF-I) and IGF-binding protein-3 (IGFBP-3) were then compared according to genotype.ResultsThe genotype distribution in the participants was 79 AA (54.1%), 60 AC (41.1%), and 7 CC (4.8%). The C allele frequency at the -202 IGFBP3 position was 25.4% in this group. The mean serum IGFBP-3 concentration in girls with the AA genotype was higher than that in girls with the AC genotype in the medium (P=0.047) and short (P=0.035) groups, respectively. There was no difference in the IGF-I to IGFBP-3 molar ratio between the AA and AC genotype groups (P=0.161).ConclusionIn conclusion, the -202 polymorphism in the IGFBP3 promoter region is assumed to affect the serum concentration of IGFBP-3 in children as well as in adults. However, it is unclear whether this affects physical development according to the concentration of IGFBP-3.